2018
DOI: 10.1002/syn.22034
|View full text |Cite
|
Sign up to set email alerts
|

Dendrites of the dorsal and ventral hippocampal CA1 pyramidal neurons of singly housed female rats exhibit lamina‐specific growths and retractions during adolescence that are responsive to pair housing

Abstract: Adolescence is accompanied by increased vulnerability to psychiatric illnesses, including anxiety, depression, schizophrenia, and eating disorders. The hippocampus is important for regulating emotional state through its ventral compartment and spatial cognition through its dorsal compartment. Previous animal studies have examined hippocampal development at stages before, after or at single time points during adolescence. However, only one study has investigated morphological changes at multiple time points dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 100 publications
(127 reference statements)
2
14
0
Order By: Relevance
“…These behavioral data indicate that the precocious dendritic arbors and spine maturity that was detected previously in the ventral hippocampus of another cohort of the EX + FR group or the retraction of dendritic arbors detected between P51-55 for another cohort of CON animals (Chen et al, 2018;Chowdhury et al, 2014) do not translate to alterations in anxiety-like behavior at P47-48 or P54-55.…”
Section: Food Restriction Effects-improvement Of Cognitive Functionsupporting
confidence: 68%
See 2 more Smart Citations
“…These behavioral data indicate that the precocious dendritic arbors and spine maturity that was detected previously in the ventral hippocampus of another cohort of the EX + FR group or the retraction of dendritic arbors detected between P51-55 for another cohort of CON animals (Chen et al, 2018;Chowdhury et al, 2014) do not translate to alterations in anxiety-like behavior at P47-48 or P54-55.…”
Section: Food Restriction Effects-improvement Of Cognitive Functionsupporting
confidence: 68%
“…One aspect of research that is relatively unexplored is the impact of voluntary physical exercise and food restriction specifically during adolescence. Previous work showed that pyramidal neurons in this brain region exhibit robust extensions and retraction of dendritic arbors during adolescence (Chen, Akad, Aderogba, Chowdhury, & Aoki, 2018;Chowdhury et al, 2014). These changes are accompanied by spinogenesis, spine pruning (Chen et al, 2018;Chowdhury et al, 2014), and restructuring of GABAergic synapses on pyramidal neurons (Aoki et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Overall, caffeine increased spine density in the NAc, mPFC, and the OFC apical dendrites while RmTBI increased spine density in the NAc, mPFC apical dendrites, OFC apical dendrites in caffeinated males, and OFC basilar dendrites in caffeinated females. Although increased dendritic spine density is commonly perceived as beneficial (Chen, ), it can often be maladaptive, particularly in the context of early adulthood neurological development. For example, a study by Kolb et al (2003) found that while exposure to amphetamine or cocaine increased spine density in the mPFC and NAc, these changes also limited the brain's ability to respond to subsequent experiences (Kolb, ).…”
Section: Discussionmentioning
confidence: 99%
“…2). Conversely, dendritic branches of pyramidal neurons in the dorsal CA1 hippocampus exhibit a transient 50% retraction during adolescence (Chen et al, 2015a). The changes in both the dorsal and ventral hippocampus are transient, returning to pre-pubertal levels by the time animals reach late adolescence.…”
Section: Anorexia Nervosamentioning
confidence: 99%